Comparison between Mycophenolate Mofetil and Azathioprine for Preventing Renal Relapse in Lupus Nephritis: An Evidence-based Case Report - Bambang Setiyohadi; Muhammad Aji Muharrom (Indonesian Journal of Rheumatology, 2018)
Background: Systemic Lupus Erythematosus (SLE) is an autoimmune disease which involved many organs. One of its severe manifestations is lupus nephritis (LN). Treatment of LN consists of two phases, induction and maintenance. Inappropriate treatment approach could increase morbidity and mortality in LN patients. Renal flare is among many bad outcomes of LN that should be mitigated with an appropriate therapeutic approach. Various guidelines stated usage of mycophenolate mofetil (MMF) or azathioprine (AZA) as an appropriate immunosuppresant in the maintenance phase. However, it is not clear which agent acts best in preventing renal flare. This paper presents a case of 21 years old SLE female patient with history of renal flare 1 month prior to admission. This study aimed to give evidence-based recommendation to adjust this patient’s therapy in order to prevent future renal flare episode.